Perceived ethnic discrimination and persecutory paranoia in individuals at ultra-high risk for psychosis. (30th July 2016) - Shaikh, Madiha; Ellett, Lyn; Dutt, Anirban; Day, Fern; Laing, Jennifer; Kroll, Jasmine; Petrella, Sabrina; McGuire, Philip; Valmaggia, Lucia R.
Abstract: Despite a consensus that psychosocial adversity plays a role in the onset of psychosis, the nature of this role in relation to persecutory paranoia remains unclear. This study examined the complex relationship between perceived ethnic discrimination and paranoid ideation in individuals at Ultra High Risk (UHR) for psychosis using a virtual reality paradigm to objectively measure paranoia. Data from 64 UHR participants and 43 healthy volunteers were analysed to investigate the relationship between perceived ethnic discrimination and persecutory ideation in a virtual reality environment. Perceived ethnic discrimination was higher in young adults at UHR in comparison to healthy controls. A positive correlation was observed between perceived ethnic discrimination and paranoid persecutory ideation in the whole sample. Perceived ethnic discrimination was not a significant predictor of paranoid persecutory ideation in the VR environment. Elevated levels of perceived ethnic discrimination are present in individuals at UHR and are consistent with current biopsychosocial models in which psychosocial adversity plays a key role in the development of psychosis and attenuated symptomatology. Highlights: Using virtual reality, we examined the relationship between perceived ethnic discrimination and paranoia in UHR. Perceived ethnic discrimination was higher in UHR group compared to controls. Perceived ethnic discrimination and paranoid persecutory ideation were positively correlated. Psychosocial adversity contributes to development of attenuated positive symptoms.